2011
DOI: 10.2147/cpt.s16972
|View full text |Cite
|
Sign up to set email alerts
|

The melatonergic system: effects on sleep and implications for the treatment of psychiatric disorders

Abstract: The circadian pacemaker or biological clock, located in the hypothalamic suprachiasmatic nucleus, is the generation site of circadian rhythms. The light/dark cycle is the circadian pacemaker's dominant synchronizing agent, though it is also influenced by neurotransmitters and the phase-shifting effects of various chemical and pharmacological components, of which melatonin (N-acetyl-5-methoxytryptamine) is the most well established. In recent years, melatonin and melatonin analogs have been commercialized in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
(97 reference statements)
0
3
0
1
Order By: Relevance
“…Unlike agomelatine, the anxiolytic effects were seen independently of the time of day of its administration (12). Since the pre-treatment with a selective melatonergic antagonist prevented the anxiolytic effect of agomelatine in the evening, but not in the morning, the anxiolytic effect may be related to the 5-HT2c antagonistic property of such a drug (13).…”
Section: Rationale For Agomelatine Treatment Ofadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike agomelatine, the anxiolytic effects were seen independently of the time of day of its administration (12). Since the pre-treatment with a selective melatonergic antagonist prevented the anxiolytic effect of agomelatine in the evening, but not in the morning, the anxiolytic effect may be related to the 5-HT2c antagonistic property of such a drug (13).…”
Section: Rationale For Agomelatine Treatment Ofadsmentioning
confidence: 99%
“…The combined actions of agomelatine on MIl/MT2 and 5-HT2c receptors facilitate the resynchronization of altered circadian rhythms and abnormal sleep patterns. Agolomelatine appears effective in treating various mood disorders (12,13).…”
Section: Characteristics Ofagomelatinementioning
confidence: 99%
“…It has been suggested that the anxiolytic effect may be related to the 5-HT2c antagonistic property of such a drug [ 47 ]. In fact, it has been demonstrated that mice genetically lacking 5-HT2c receptors showed reduced anxiety, whereas in other experimental models, 5-HT2c receptor agonists show anxiogenic properties [ 48 ]. The antagonism of 5-HT2c receptors induced by agomelatine especially in the amygdala and hippocampus may be associated with anxiolytic properties [ 49 ] and, always through the blockade of 5-HT2c receptors, agomelatine may also enhance extracellular levels of noradrenaline (NA) in hippocampus, therefore increasing anxiolytic response [ 50 ].…”
Section: Agomelatine In the Treatment Of Anxiety Disorders (Ads)mentioning
confidence: 99%
“…Кроме того, длительное повышение уровня норадреналина в лобных долях способствует развитию противоболевого эффекта, механизм которого аналогичен таковому СИОЗСиН, но без воздействия на обратный захват нейротрансмиттеров [44] 5 . Существуют экспериментальные данные об анксиолитическом эффекте блокады 5-HT2C-рецепторов: у мышей с генетическим дефектом этого типа рецепторов отмечался патологически низкий уровень тревоги, а некоторые агонисты оказывали протревожное действие [45].…”
unclassified